RORγt antagonist suppresses M3 muscarinic acetylcholine receptor-induced Sjögren's syndrome-like sialadenitis. (11th October 2016) - Tahara, M; Tsuboi, H; Segawa, S; Asashima, H; Iizuka-Koga, M; Hirota, T; Takahashi, H; Kondo, Y; Matsui, M; Matsumoto, I; Sumida, T
Summary: We showed recently that M3 muscarinic acetylcholine receptor (M3R)-reactive CD3 + T cells play a pathogenic role in the development of murine autoimmune sialadenitis (MIS), which mimics Sjögren's syndrome (SS). The aim of this study was to determine the effectiveness and mechanism of action of retinoic acid-related orphan receptor-gamma t (RORγt) antagonist (A213) in MIS. Splenocytes from M3R knockout (M3R –/– ) mice immunized with murine M3R peptide mixture were inoculated into recombination-activating gene 1 knockout (Rag-1 –/– ) mice (M3R –/– →Rag-1 –/– ) with MIS. Immunized M3R –/– mice (pretransfer treatment) and M3R –/– →Rag-1 –/– mice (post-transfer treatment) were treated with A213 every 3 days. Salivary volume, severity of sialadenitis and cytokine production from M3R peptide-stimulated splenocytes and lymph node cells were examined. Effects of A213 on cytokine production were analysed by enzyme-linked immunosorbent assay (ELISA) and on T helper type 1 (Th1), Th17 and Th2 differentiation from CD4 + T cells by flow cytometry. Pretransfer A213 treatment maintained salivary volume, improved MIS and reduced interferon (IFN)-γ and interleukin (IL)-17 production significantly compared with phosphate-buffered saline (PBS) ( P  < 0·05). These suppressive effects involved CD4 + T cells rather than CD11c + cells. Post-transfer treatment with A213 increased salivary volume ( P  < 0·05), suppressed MIS ( P  < 0·005) and reduced IFN-γ and IL-17 production ( P  < 0·05). In vitro, A213 suppressed IFN-γ and IL-17 production from M3R-stimulated splenocytes and CD4 + T cells of immunized M3R –/– mice ( P  < 0·05). In contrast with M3R specific responses, A213 suppressed only IL-17 production from Th17 differentiated CD4 + T cells without any effect on Th1 and Th2 differentiation in vitro . Our findings suggested that RORγt antagonism is potentially suitable treatment strategy for SS-like sialadenitis through suppression of IL-17 and IFN-γ production by M3R-specific T cells. Graphical Abstract: